DRIS norms for 'Valencia' sweet orange on three rootstocks - Filho, Francisco de Assis Alves Mourão; Azevedo, João Carlos (Pesquisa Agropecuaria Brasileira, 2003)
Diagnosis and Recommendation Integrated System (DRIS) applies nutrient ratios instead of the isolated concentration values of each nutrient in interpretation of tissue analysis. The objectives of this research were to establish adequate DRIS norms for 'Valencia' sweet orange irrigated commercial groves budded on three rootstocks and correlate indexes of nutrition balance with yield. Experiments were conducted in São Paulo State, Brazil. Rootstocks Rangpur lime, Caipira sweet orange, and Poncirus trifoliata, with more than six years old and yield above 40 ton ha-1 were utilized. Data referred to yield, tree spacing, rootstock and foliar concentrations of N, P, K, Ca, Mg, S, Fe, Mn, Cu, Zn, and B in non fruiting terminals for each grove were processed for the years 1994 through 1998. DRIS indexes were calculated by Nick criterion for choosing the ratio order of the nutrients and Jones calculation method of the ratio functions. Indexes of nutritional balance calculated from DRIS norms presented high correlation with yield for the three scion/rootstock combinations. DRIS norms defined in this research are valid, since leaf sampling is done on non fruiting terminals and the grove is irrigated.
Keywords: citrus; foliar diagnosis; nutrient balance; plant nutrition